Subcellular trace element distribution in Geosiphon pyriforme - Maetz, Mischa; Traxel, Kurt (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 1999)
Geosiphon pyriforme is a unique endosymbiotic consortium consisting of a soil dwelling fungus and the cyanobacterium Nostoc punctiforme. At present this symbiosis becomes very interesting because of its phylogenetic relationship to the arbuscular mycorrhizal (AM) fungi. Geosiphon pyriforme could be an important model system for these obligate symbiotic fungi, which supply 80-90% of all land plant species with nutrients, in particular phosphorous and trace elements. Combined PIXE and STIM analyses of the various compartments of Geosiphon give hints for the matter exchange between the symbiotic partners and their environment and the kind of nutrient storage and acquisition, in particular related to nitrogen fixation and metabolism. To determine the quality of our PIXE results we analysed several geological and biological standards over a time period of three years. This led to an overall precision of about 6% and an accuracy of 5-10% for nearly all detectable elements. In combination with the correction model for the occurring mass loss during the analyses this holds true even for biological targets.